(untitled) - Varian, Hal R. (Cambridge,New York, 2004)
The Economics of Information Technology is a concise and accessible review of important economic factors affecting information technology industries. These industries are characterized by high fixed costs and low marginal costs of production, large switching costs for users, and strong network effects. Hal Varian outlines the basic economics of these industries while Joseph Farrell and Carl Shapiro describe the impact of these factors on competition policy. The volume is an ideal introduction for undergraduate and graduate students in economics, business strategy, law and related areas
Keywords: Information technology,Computer industry,Công nghệ thông tin,Công nghiệp máy tính; Economic aspects,Khía cạnh kinh tế